2009
DOI: 10.1080/13803390903313556
|View full text |Cite
|
Sign up to set email alerts
|

Intact first- and second-order implicit sequence learning in secondary-school-aged children with developmental dyslexia

Abstract: We examined the influence of task complexity on implicit sequence learning in secondary-school-aged children with developmental dyslexia (DD). This was done to determine whether automatization problems in reading extend to the automatization of all skill and depend on the complexity of the to-be-learned skill. A total of 28 dyslexic children between 12 and 15 years and 28 matched control children carried out two serial reaction time tasks using a first-order conditional (FOC) and second-order conditional (SOC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 64 publications
3
47
0
Order By: Relevance
“…Nevertheless, the lack of significant effects early in learning is interesting in light of the inconsistent results of previous studies. Indeed, all of the three studies that have reported intact implicit sequence learning in children with DD (Deroost et al, 2010;Menghini et al, 2010;Waber et al, 2003) have focused on a relatively narrow practice interval (ranging from 24 to 104 repetitions of the sequential pattern compared with the 250 repetitions in the present study) given within a single practice session. In light of the fact that a significant group difference in the present study emerged only in day 2, after more than 200 repetitions of the sequence, it is possible that group differences may have been revealed if the studies above had included a wider practice interval.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, the lack of significant effects early in learning is interesting in light of the inconsistent results of previous studies. Indeed, all of the three studies that have reported intact implicit sequence learning in children with DD (Deroost et al, 2010;Menghini et al, 2010;Waber et al, 2003) have focused on a relatively narrow practice interval (ranging from 24 to 104 repetitions of the sequential pattern compared with the 250 repetitions in the present study) given within a single practice session. In light of the fact that a significant group difference in the present study emerged only in day 2, after more than 200 repetitions of the sequence, it is possible that group differences may have been revealed if the studies above had included a wider practice interval.…”
Section: Discussionmentioning
confidence: 97%
“…Although the majority of published studies have found a sequence learning deficit in adults (Du & Kelly, 2013;Howard et al, 2006;Menghini, Hagberg, Caltagirone, Petrosini, & Vicaria, 2006;Stoodley, Harrison, & Stein, 2006) and children (JimenezFernandez et al, 2011;Vicari et al, 2003Vicari et al, , 2005 with DD, intact performance has also been reported (Deroost et al, 2010;Kelly, Griffiths, & Frith, 2002;Russeler, Gerth, & Munte, 2006).…”
mentioning
confidence: 91%
“…The task varies in a number of respects. For instance, the length of training, for example, as measured by the number of exposures to the sequence (number of blocks times number of sequences per block), has varied substantially between studies, from as little as 10 (Stoodley et al, 2006) to as much as 108 (Deroost et al, 2010). Learning via the procedural memory system requires practice or repeated exposures to information (Packard & Knowlton, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Children who had been diagnosed as dyslexic did not benefit from the sequential pattern to speed their responses, whereas normal readers seemed to do so. However, not all studies support the idea that children with reading difficulties have a general deficit in implicit statistical learning (Deroost et al, 2010; Menghini, Finzi, & Benassi, 2010; Roodenrys & Dunn, 2008; Waber et al, 2003). Moreover, some researchers (Jiménez-Fernández et al, 2011) have raised questions about some of the laboratory tasks that have been used to assess implicit learning, including the sequence learning task used by Vicari et al (2003) and others.…”
mentioning
confidence: 97%